Conservation Subdivision: Post-construction Phase—Policy Directions and the Importance of Assessing Stakeholder Opinions - Daniel Feinberg; Mark Hostetler (EDIS)
Simply designating open space in a development is not enough to provide long-term protection for a variety of wildlife. New policies need to be developed that encourage developers of conservation developments to adopt long-term management practices that support biodiversity conservation. This 5-page fact sheet discusses policy options that could be used to support conservation management practices and reports on a survey of Colorado landowners who have created conservation developments and their opinions about a policy option to support the implementation of management practices. Written by Daniel Feinberg and Mark Hostetler, and published by the UF Department of Wildlife Ecology and Conservation, December 2014. (Photo credit: Daniel Feinberg)